Sobolev, Sergei Vasil'evich (retired officer, vice-chairman of the NGO 'Shield to Chernobyl')
About the organization which helps Belarus liquidators from the army and police forces; inability of the civil and military authorities to organize decontamination work in a safe way; about firemen who extinguished the blaze at the reactor right after the explosion; about the Ignatenko family; continuing ignorance about radiation.